Inhibition of Angiotensin Converting Enzyme Impairs Anti-staphylococcal Immune Function in a Preclinical Model of Implant Infection - Trikha, Rishi; Greig, Danielle; Kelley, Benjamin V.; Mamouei, Zeinab; Sekimura, Troy; Cevallos, Nicolas; Olson, Thomas; Chaudry, Ameen; Magyar, Clara; Leisman, Daniel; Stavrakis, Alexandra; Yeaman, Michael R.; et al. (Frontiers in Immunology, 2020)
Background: Evidence suggests the renin-angiotensin system (RAS) plays key immunomodulatory roles. In particular, angiotensin-converting enzyme (ACE) has been shown to play a role in antimicrobial host defense. ACE inhibitors (ACEi) and angiotensin receptor blockers (ARB) are some of the most commonly prescribed medications, especially in patients undergoing invasive surgery. Thus, the current study assessed the immunomodulatory effect of RAS-modulation in a preclinical model of implant infection. Methods: In vitro antimicrobial effects of ACEi and ARBs were first assessed. C57BL/6J mice subsequently received either an ACEi (lisinopril; 16mg/kg/day), an ARB (losartan; 30mg/kg/day), or no treatment. Conditioned mice blood was then utilized to quantify respiratory burst function as well as Staphylococcus aureus Xen36 burden ex vivo in each treatment group. S. aureus infectious burden for each treatment group was then assessed in vivo using a validated mouse model of implant infection. Real-time quantitation of infectious burden via bioluminescent imaging over the course of 28 days post-procedure was assessed. Host response via monocyte and neutrophil infiltration within paraspinal and spleen tissue was quantified by immunohistochemistry for F4/80 and myeloperoxidase, respectively. Results: Blood from mice treated with an ACEi demonstrated a decreased ability to eradicate bacteria when mixed with Xen36 as significantly higher levels of colony forming units (CFU) and biofilm formation was appreciated ex vivo (p<0.05). Mice treated with an ACEi showed a higher infection burden in vivo at all times (p<0.05) and significantly higher CFUs of bacteria on both implant and paraspinal tissue at the time of sacrifice (p<0.05 for each comparison). There was also significantly decreased infiltration and respiratory burst function of immune effector cells in the ACEi group (p<0.05). Conclusion: ACEi, but not ARB, treatment resulted in increased S. aureus burden and impaired immune response in a preclinical model of implant infection. These results suggest that perioperative ACEi use may represent a previously unappreciated risk factor for surgical site infection. Given the relative interchangeability of ACEi and ARB from a cardiovascular standpoint, this risk factor may be modifiable.